The inclusion behaviour of "wheel-and-axle" host compounds - Johnson, Louise (Department of Chemistry, 2017)
The inclusion behaviour of three "wheel-and-axle" host molecules was investigated. By virtue of their shape and the way in which they pack these host molecules are able to entrap guest molecules into a host-guest array. The host compounds were: 1,1,6,6-tetraphenyl-hexa-2,4-diyne-1,6-diol (HOST1), 4,4'-bis(diphenylhydroxymethyl)biphenyl (WEB11 ), 4,4'-bis(diphenylmethyl)biphenyl (WEB10). The WEB 11 host compound was found not to include guest molecules. The crystal structures of the non-porous α-phases of these three host compounds and the inclusion compounds were elucidated using single crystal X-ray diffraction methods. Both the dial hosts were found to form hydrogen bonded host-guest inclusion compounds with guests able to accept hydrogen bonds such as ketones. In these compounds there was host-guest hydrogen bonding and the hydroxy moieties of the host molecules adopted a trans conformation. Host-host intermolecular hydrogen bonding existed in inclusion compounds containing guests unable to function as hydrogen bond acceptors. The host hydroxy moieties adopted a gauche conformation in order to allow host-host hydrogen bonding. Hydrogen bond formation was the directing force determining the form of the host-guest molecular array. The mechanism and kinetics of a solid-solid reaction between the host1 compound and benzophenone were investigated and electron microscopy showed the external habit of host1 α-phase to play an important role in propagating the reaction. The kinetics of the reaction occurring between solid host1 and acetone vapour was studied and an activation energy calculated. The kinetic behaviour of host1 could be explained in terms of exposed hydroxy moieties on the bc plane of the host1 α-phase. Thermal analysis techniques were used to investigate the stability of these host-guest compounds. Thermogravimetry was used to evaluate the precise stoicheoimetry of the host-guest compounds as well as the complexity of their thermal decay. DSC was used to measure the enthalpies of thermal decomposition and to evaluate the strength with which the guest was held in the lattice. Correlation between thermal stability and the structure of these compounds was attempted and the results were encouraging. The problem lay in obtaining reliable values of the enthalpies of the guest release, a difficult task when dealing with compounds which are highly unstable at room temperature. [Corrected PDFcompleted 14/11/20106]